Efficient synthesis of (2S)-tert-butyl 2-(2-bromopropanamido)-5-oxo-5-(tritylamino)pentanoate as a precursor of PET radiotracer [18F]FPGLN. Issue 12 (18th June 2017) - Liu, Shaoyu; Tang, Xiaolan; Nie, Dahong; Jiang, Shende; Tang, Ganghua
ABSTRACT: This study describes a convenient protocol for the synthesis of (2 S )- tert -butyl 2-(2-bromopropanamido)-5-oxo-5-(tritylamino)pentanoate, which can serve as an appropriate precursor of (2 S )-5-amino-2-(2-[ 18 F]fluoropropanamido)-5-oxopentanoic acid ( N -(2-[ 18 F]fluoropropionyl)-L -glutamine, [ 18 F]FPGLN) for tumor positron emission tomography imaging. Five-step synthesis starting fromL -glutamine provided the desired precursor with high yields. In addition, a simple method for the preparation of [ 18 F]FPGLN from this easily available precursor was developed using a two-step 18 F-labeling strategy. GRAPHICAL ABSTRACT: